Unexpected expansion: Climate change-induced movement of the Cream-colored Courser (Cursorius cursor) into Central Anatolia - Evcin, Özkan (Turkish Journal of Forestry, 2024)
Climate change is one of the major threats that negatively affects wildlife species and habitats. In recent years, global temperatures have increased, extreme climate events have become more frequent, and many bird species have experienced changes in their geographic ranges, behaviors, and life cycles in response to these environmental changes. The Cream-colored Courser (Cursorius cursor), a ground-nesting desert bird from the Glareolidae family, is a bird species that has begun to show changes in its distribution and phenology due to climate change. Normally living in arid environments in the Eastern Palearctic, this species has recently started to be observed in new areas far from its normal range, including Central Anatolia in Türkiye. In recent years, the unexpected appearance and nesting of this species in Tuz Lake, now located in central Türkiye, has raised concerns among conservationists and highlighted the species' vulnerability to climate change. This study aims to model the potential future distribution of the Cream-Coated Courser in Türkiye under two climate change scenarios (SSP 4.5 and SSP 8.5) over three time periods: 2021-2040, 2041-2060 and 2061-2080. Using MaxEnt modeling and climate change projections, the study will identify and interpret the key climatic factors driving these changes in distribution. Our findings will provide critical insights into the future range dynamics of the species and inform conservation strategies to reduce the impacts of climate change on this and other vulnerable bird species.
Keywords: Climate change; Cream-colored courser; Ecological modeling; Anatolia; Ornithology; Türkiye; Orman Biyoçeşitliliği; Forest Biodiversity; İklim değişikliği; Çöl koşarı; Ekolojik modelleme; Anadolu; Ornitoloji; Türkiye